2021
DOI: 10.1002/pa.2632
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating economy via fiscal package: The only way out to save vulnerable Workers' lives and livelihood in Covid‐19 pandemic

Abstract: This paper examines critically the economic package announced by the Indian central government to counter the challenges of lives and livelihood in the Covid‐19 pandemic. This paper estimates the shares of the fiscal economic packages in two phases as per the shares of the vulnerable workers and number of Covid‐19 cases in the Indian states. The recent data on labour market are used from National Sample Survey Organization and data on Covid‐19 cases from Ministry of Health and Family Welfare. This paper recomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Many scholars have therefore called for governments to strengthen social security measures including access to childcare, healthcare and economic support beyond those with formal employment (WHO Regional Office for Europe, 2020; Azeez et al, 2021;Bassier et al, 2021;Thakur et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have therefore called for governments to strengthen social security measures including access to childcare, healthcare and economic support beyond those with formal employment (WHO Regional Office for Europe, 2020; Azeez et al, 2021;Bassier et al, 2021;Thakur et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, this strategic policy choice of sending migrant workers to their home has been questioned by many authors on theoretical grounds of labour economics, for example there can be uncertainty for workers returning to their state of domicile who may find it difficult to have agriculture-based jobs that may be available in the longer run (Breman, 2020 ), whereas some other authors have also admitted the helplessness of the situation. Another debate is the fiscal choices (Thakur & Kumar, 2021 ) or their limitation (Jose et al, 2020 ) in the aftermath of the pandemic. On May 13, 2020, the central Government of India announced a stimulus package called “Atmanirbhar Bharat” or “Self-reliant India”.…”
Section: Implications Of the Resultsmentioning
confidence: 99%
“…One of the proposed sub-strategic choices (allowing migrant workers to stay in their homes in their workplace states) requires stimulus help from governmental bodies. Many notable economists questioned similar fiscal stimulus packages about their functionality in a monetarist economy, but the authors Thakur and Kumar ( 2021 ) concluded similar fiscal expansion would be the only way out due to the severity of the situation. Our models offer the flexibility of a strategic choice without any monotonous dominance of strategy over another which can offer a more practical solution.…”
Section: Implications Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To begin with, advanced economies appear to have abandoned the fiscal tightening reforms seeking to bring down public debt to embrace expansionary macroeconomic policies for as long as it takes for the private sector to regain its confidence to spend. Similarly, through significant fiscal stimulus, most governments have shown themselves willing to engage in deficit spending for the coming years for the sake of avoiding a double-dip recession (Thakur & Kumar, 2021). Beyond public spending, as Ferrannini et al (2021) note, industrial and innovation policies, together with the reversal of wage repression, will be required to raise productivity growth, while strong(er) labour market institutions seem a precondition to the alignment of wages with productivity, the support for structural change and the reduction of (income) inequalities.…”
Section: When Economics Come Into Play: Revitalising Multilateralism ...mentioning
confidence: 99%